Quality of Understanding in Communication among and between Political Parties, Mass Media, and Citizens: An Empirical Study of the 2013 Austrian National Election - Uta Russmann (Journal of Deliberative Democracy)
The study investigates the extent to which political parties, the mass media, and citizens follow qualitative principles demanded by the public sphere concept in political campaign communications. Using the index of a quality of understanding (IQU), it analyses the press releases and Facebook posts of political parties, newspaper articles, and responses by citizens in the form of comments in newspaper forums and on parties’ Facebook pages (N=7,525) during the 2013 Austrian national election. Considering that the quality of understanding of public discourse is measured on a 100-point scale, which serves as a benchmark representing perfect understanding, observed real-world values are often rather low. Austrian political parties scored the highest IQU of 28.35 points, and hence can be described as most closely following the principles of an ideal communication orientation. The quality of understanding is the lowest in everyday political discussion on Facebook, where political parties’ posts have an IQU of 17.97 points. The difference of 10.38 points to the highest achieved value of 28.35 reveals different deliberative communication practices between well-considered and strategically formulated communication in press releases as well as newspaper articles and everyday communication including citizens’ comments on Facebook and newspaper articles, which take different configurations.